Strategies of the Palu City Health Office in Achieving a Healthy City - Fadly Umar; Muhammad Khairil; Ardi Munir (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: This study aimed to analyze the strategies implemented by the Health Office of Palu City in realizing a Healthy City, as part of Indonesia’s national movement toward achieving the World Health Organization (WHO) Healthy City framework. The program emphasizes cross-sector collaboration and active community participation, which remain crucial in addressing challenges of urbanization, social inequality, and limited health infrastructure. Methods: A qualitative case study design guided by Parsons’ AGIL functional framework was applied to explore adaptive, integrative, goal-oriented, and latent dimensions of health governance. Data were collected through in-depth interviews, observations, and document reviews involving key stakeholders such as health officials, community leaders, health cadres, and social organizations (e.g., PKK and NGOs). Data were analyzed thematically using NVivo 12 Plus. Ethical clearance was obtained, and all participants provided informed consent. Results: The findings revealed that the Health Office strategies were categorized into the four AGIL functional dimensions: (1) Adaptation, through fiscal adjustment and program prioritization; (2) Integration, via inter-sectoral coordination and disaster response mechanisms; (3) Goal Attainment, through leadership alignment with municipal health targets; and (4) Latency, through sustained community participation and cadre-led education. These strategies strengthened social structures, communication forums, and community-based initiatives such as GERMAS and open defecation elimination. Despite these efforts, key barriers persisted—namely, limited budget allocation, weak cross-sectoral institutionalization, and uneven citizen engagement across subdistricts. Conclusion: The study concludes that a socially grounded, AGIL-informed collaborative strategy adopted by the Health Office is effective in promoting the WHO Healthy City initiative within Indonesia’s decentralized governance context. These findings contribute theoretically to the discourse on social determinants of health and systems theory, and offer practical implications for strengthening local government capacity, budgeting, and inter-sectoral health policies.